2016
DOI: 10.5888/pcd13.160130
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Fruit and Vegetable Intake by Race/Ethnicity and by Hispanic Origin and Nativity Among Women in the Special Supplemental Nutrition Program for Women, Infants, and Children, 2015

Abstract: IntroductionThe objective of this exploratory study was to determine whether fruit and vegetable consumption differed by race/ethnicity, by origin and nativity among Hispanics, and by language preference (as an indicator of acculturation) among foreign-born Hispanics.MethodsWe recruited 723 women enrolled in the Special Supplemental Nutrition Program for Women, Infants and Children (WIC) and orally administered a questionnaire containing demographic items, validated measures of food security status and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…We also observed greater legume intake among Hispanic children, which may be related to the higher fiber intake. The greater legume intake among Hispanic children in this nationally representative sample is consistent with findings from regional studies of adult women participating in WIC [25], suggesting that Hispanic women and children have similar dietary behaviors that involve greater legume intake compared to their respective non-Hispanic White counterparts. For potassium intake, it is unclear which foods are driving the higher potassium intake among Hispanic children, though it is possible that this is also related to dairy consumption, as milk is a key source of potassium [26].…”
Section: Discussionsupporting
confidence: 82%
“…We also observed greater legume intake among Hispanic children, which may be related to the higher fiber intake. The greater legume intake among Hispanic children in this nationally representative sample is consistent with findings from regional studies of adult women participating in WIC [25], suggesting that Hispanic women and children have similar dietary behaviors that involve greater legume intake compared to their respective non-Hispanic White counterparts. For potassium intake, it is unclear which foods are driving the higher potassium intake among Hispanic children, though it is possible that this is also related to dairy consumption, as milk is a key source of potassium [26].…”
Section: Discussionsupporting
confidence: 82%
“…Fewer consistencies were noted between NHB and NHW although several studies reported greater SSB and sugar purchasing among NHB compared to NHW. These findings align with the dietary consumption literature, which continues to highlight significant racial/ethnic differences in intake among adults and children [ 8 , 10 , 54 , 55 , 56 ]. Additional studies are needed to establish consistent patterns in food and beverage purchasing by racial/ethnic group.…”
Section: Discussion and Future Directionssupporting
confidence: 86%
“…Future studies should evaluate consumer food and/or beverage purchases across a greater variety of racial/ethnic groups (i.e., non-Hispanic Asian, Native American, Pacific Islander, etc.). Given the heterogeneous composition of all races and ethnicities, future studies could conduct robust assessments of purchasing within groups, which will permit the study of characteristics such as acculturation and nativity—two factors that are often considered in studies of diet quality [ 55 , 56 ]. In recent years, public health research has placed greater emphasis on socio-political factors that create racial/ethnic inequities in health such as structural and systemic racism [ 57 ].…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) is a federal nutrition assistance program that provides supplemental, nutrient-dense foods and beverages, nutrition education, and referrals to social/medical services for eligible pregnant, post-partum, and breastfeeding women up to their fifth birthday. 1 A limited number of studies have explored the relationship between race/ethnicity and dietary intake among WIC women, [2][3][4] but these studies are limited in generalizability, and differences in nutrients/food groups commonly under-/overconsumed by WIC women remain unknown. Therefore, the objective of this study was to use nationally representative data to examine racial/ethnic differences in dietary intake of women living in WICparticipating households, with a focus on the priority nutrients and food groups described in the 2017 report by the National Academies of Sciences, Engineering, and Medicine (NASEM).…”
mentioning
confidence: 99%